New date on the structure of the north-east part of the central Kazakhstan devonian volcanic belt; Doklady Akademii Nauk; Vol. 358, N 1 - Kurchavov A. M.; Grankin M. S.; Mal'chenko E. G.; Zhukovskii V. I.; Mazurov A. K. Aleksey Karpovich; Khamzin S. Kh. (1998, 1998)
В фонде НТБ ТПУ отсутствует